OPTIMALISASI KEMAHIRAN PEMBAWA ACARA YANG TERAMPIL MELALUI PRAKTIK PUBLIC SPEAKING - Purnama Yasa, I Komang Widya (IAHN Gde Pudja Mataram, 2024)
This research aims to optimize the ability of students to be ready to face the demands of communication in the contemporary era. The research location is on the campus of the Institut Agama Hindu Negeri Gde Pudja Mataram. This research is designed in qualitative descriptive, using Constructivism theory and Public Communication theory. The results showed that the learning dynamics describe a dynamic, learner-centered process, and focus on deep understanding so that students become active, critical, and independent, while understanding that learning is not only about accumulating facts, but also about meaningful knowledge construction. Communication ethics plays an important role in building individuals as presenters based on moral norms and principles that govern how to speak, listen, and interact with others. Through the practice of public speaking as an optimization of proficiency in communication helps students become presenters by developing speaking skills, overcoming stage anxiety, understanding the audience, and stimulating creativity in communication. Good self-expression makes the host more skillful and effective so as to create a connection with the audience, make communication more interesting, and express commitment to the message conveyed.